A classification to align social-ecological land systems research with policy in Europe. (December 2018) - Winkler, Klara J.; Scown, Murray W.; Nicholas, Kimberly A.
Highlights: We propose a classification to orient integrated social-environmental land systems research along policy and research interests. We review 69 papers on European rural land systems research. We find research focuses on more environmental variables, while policy focuses more on social (especially economic) goals. Policy is less focused on underlying environmental aspects (e.g., topography). Land systems research could explore human health and air quality variables. Abstract: Both research and policy recognize land systems as fundamental to human life and activities. However, these two perspectives approach land from different ends and it can be difficult to see how studied variables contribute to broader policy goals. In this paper, we argue that there is a need to better select variables to study land systems as social-ecological systems, and to align research more with those policy goals. Concentrating on the European continent, we pursue three interrelated objectives: we (1) build a classification of land systems variables, (2) examine where existing land systems research is positioned in this classification, and (3) compare a set of policies and science-policy frameworks with the classified research. To do so, we conduct a systematic review of 69 peer-reviewed, empirical land systems papers, as well as four overarching policies and science-policy frameworks. We find that over 60% of the reviewed papers include both environmental and social variables, and we identify 154 unique variables studied, 57% of which are environmental. The average paper examines four times as many environmental variables as social ones. We find that policies and science-policy frameworks stress social variables more and include health and air quality aspects that are lacking in the reviewed land systems research. Our classification can help to design research that includes both social and environmental variables and is aligned with broader policy goals. We highlight social variables with available spatial data to encourage a more balanced and integrative social-ecological research design, going beyond a focus on the built and natural environment. Our classification can contribute to guiding land systems researchers towards greater policy relevance. We hope that our classification contributes to a conversation within land systems research on the selection of variables, as well as its further development.